FENOMENA ANAK HASIL KLONING DALAM TINJAUAN HUKUM ISLAM DAN FIQIH KONTEMPORER - Umi Hani (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2016)
Cloning of humans is a successful Western scientists in utilizing science finally able to make a rapid progress that has outpaced all human forecasts . Imagine, in this way be considered as a way to improve the quality of offspring : a more intelligent, strong, handsome, or to reproduce offspring without the need for conventional breeding process . However, in Islam there is no that does not allow therefore the issue needs to be revisited. Therefore the aim of this study was to determine custody of a child cloned in Contemporary Islamic law and jurisprudence, and then to see the inheritance rights of a child cloned in Contemporary Fiqh and Islamic law . This research method uses a qualitative approach method with library research. Materials used in the study of law is the primary legal materials , legal materials and secondary legal materials tertiary . The method of data analysis used in this study is descriptive analytical method .Based on the research results according to Islamic law are forbidden because the cloning process would prevent the implementation of many laws of Personality ' , such as the law of marriage , lineage , livelihood , rights and obligations between father and son , inheritance , child care , relationships forbidden, actuator connect gan ' asbabah , and others and violate nature that God has created man in trouble for child birth . Human cloning is really a horrible act, which will be turned over turned the structure of people's lives . According to contemporary Fikh law allowed because it can help the child process on a family and give happiness to them . The person should preferably be done by doing cloning legitimate husband and wife, which in no way could have inherited with cloning. Before doing cloning should couples to consulate with the doctor.